Estudo do comportamento de almofadas elastoméricas sob vigas pré-moldadas e análise da estabilidade lateral após a montagem - Reis, Leandro Cesar dos (2018)
Precast concrete girders on bearing pads are subjected to instability depending on several variables such as span length, initial imperfections, especially initial lateral sweep, and bearing pads behavior, regarding to stiffnesses and dimensions. On this work, numerical models are developed in the ANSYS Workbench 18.0 in order to assess the instability limit loads and the rotational stiffnesses of the pads in many combinations of span length, cross section of the girder and lateral sweep. Then, it was also evaluated the lift off phenomenon of the girder on the supports and the variation of stiffnesses in which situation. Finally, the variations of the limit loads considering changes in the bottom and top flanges dimensions is considered. The proposed models properly represented the girders over the bearing pads once the behavior are validated by experimental studies of the literature. The increase in spans and initial imperfections causes a decrease in the rollover limit load. The lift off effect is aggravated as the lateral eccentricities increase and also depends on the initial compression of the bearing pad. In the analyzed combinations, the reduction of the rotational stiffness is about 37% for the critical situation, which span length about 40 m and lateral sweep of L/300, with loss of contact between 50% and 60%. Variations of top and bottom flanges width, changing lateral moments of inertia, tend to vary the rollover limit load. Increasing the lateral inertia in about 35% results in an increase of 24% for the limit load for the cases analyzed in this study.